Respuesta :

Step-by-step explanation:

Step 1:  Write the equation using point-slope form

Point-Slope Form:  [tex]y-y_{1}=m\left(x-x_{1}\right)[/tex]

[tex]y-0=m(x-3)[/tex]

[tex]y = m(x-3)[/tex]

Step 2:  Find the slope

[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]

[tex]m=\frac{-2-0}{-2-(-3)}[/tex]

[tex]m=\frac{-2}{1}[/tex]

[tex]m=-2[/tex]

Step 3:  Combine them together

[tex]y = m(x - 3)[/tex]

y = -2(x - 3)

IF NEEDED:  Completely factor

[tex]y = (-2 * x) + (-2 * -3)[/tex]

y = -2x + 6

ACCESS MORE